A Study Of English Usage In Social Media By University Students (A Case Study Of English Department Students Of Tadulako University) - Muhammad Fadhil Irawan Hadi; Darmawan, Darmawan; Wahyudin, Wahyudin; Mochtar Marhum (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2025)
The objective of this research is to find out how English department students of Tadulako University perceive the use of social media for learning English. This research is a convergent mixed method research focusing in case study design. The participants of this research were twenty active English department students selected using snowball technique. The data was collected through Google form questionnaires and a follow-up interview. The findings of this research revealed that, the students perceive learning English through social media positively. It created a stress-free environment with abundant resources to enhance all of their language skills. However network related problems, distracting advertisements and inappropriate contents still present some challenges.